Factors increasing the risk of flap complications following pectoralis major myocutaneous flap reconstruction for head and neck cancers - Shanmugam, Subbiah; Hussain, Syed Afroze; Michael, Rajiv (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Oral cavity cancer is one of the most common cancers and a leading cause of cancer death in India. Pectoralis major myocutaneous flaps (PMMC) are still widely used for reconstruction of defects in the head and neck, though microvascular free flaps are the ‘gold standard’. This study was aimed to identify the risk factors involved in increasing the post-operative PMMC flap complications. Methods: Patients who underwent surgical resection of primary head and neck cancer with PMMC flap reconstruction were included and their demographic data, pre-operative laboratory values, surgery details and post-operative flap morbidity were collected retrospectively from the master case sheets from January 2013 to December 2019. Factors such as age, gender, stage of disease, pre-operative anemia, hypoprotenemia and radiation therapy, presence of diabetes and size of the flaps were analysed to find their relation in causing flap complications. Results: Totally 285 patients were included for analysis and 9.82% (n=28) had major flap complications. On analysis we found that pre-operative hypoproteinemia (serum albumin <3.5) (p=0.001) and prior radiation therapy (p=0.02) significantly increased the risk of flap complications. Similarly, patients with larger bipaddled flaps had higher flap complication rates (p=0.0002) and previous radiation treatment further increased the major complication rates in bipaddle flaps. Conclusions: PMMC flaps are still a viable option for head and neck reconstruction especially in patients with multiple comorbidities and where free microvascular flaps are not done routinely. Careful patient selection, pre-operative optimisation and good post-operative care will help to reduce flap complications.